Estimation of Groundwater Potential at Khalid Bin Walid Boarding School Using the Schlumberger Configuration Geoelectric Method - Ika Daruwati; Rindi Genesa Hatika; Sohibun Sohibun; Hamid Syahropi; Azmi Asra; Nurhikmah Sasna Junaidi; Meilan Demulawa (Postgraduate, University of Mataram, 2023)
Khalid Bin Walid Islamic Boarding School is one of the Islamic boarding schools in Rokan Hulu Regency. This school is located in a water crisis area with complex groundwater sources. This study aims to determine the potential of groundwater as a reference for drilling wells and to determine the structure of the subsurface layer by using the geoelectrical method. The geoelectrical method is a method that is widely used, and the results are promising, namely, to obtain an overview of the subsurface soil layers and the possibility of groundwater presence. The configuration used in this study is the Schlumberger configuration using the basic principle of current propagating in the earth when injected in all directions and the assumption that the potential of the subsurface rock layer is the same. Data will be collected on four tracks, with a track length of 100-200 m. From the data processing results, it was found that potential sources of groundwater on track 3 with a depth of 13.7–30.3 m with alluvium rocks were suspected. Groundwater on this track can be used as a source of clean water using drilling.